Mitochondrial dysfunction and Alzheimer's disease: prospects for therapeutic intervention - Lim, Ji Woong; Lee, Jiyoun; Pae, Ae Nim (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2020)
Alzheimer's disease (AD) is a multifactorial neurodegenerative disease and has become a major socioeconomic issue in many developed countries. Currently available therapeutic agents for AD provide only symptomatic treatments, mainly because the complete mechanism of the AD pathogenesis is still unclear. Although several different hypotheses have been proposed, mitochondrial dysfunction has gathered interest because of its profound effect on brain bioenergetics and neuronal survival in the pathophysiology of AD. Various therapeutic agents targeting the mitochondrial pathways associated with AD have been developed over the past decade. Although most of these agents are still early in the clinical development process, they are used to restore mitochondrial function, which provides an alternative therapeutic strategy that is likely to slow the progression of the disease. In this mini review, we will survey the AD-related mitochondrial pathways and their small-molecule modulators that have therapeutic potential. We will focus on recently reported examples, and also overview the current challenges and future perspectives of ongoing research.
Keywords: SMALL-MOLECULE INHIBITORS; TRANSGENIC MOUSE MODEL; STRUCTURE-BASED DESIGN; A-BETA; AMYLOID-BETA; CYCLOPHILIN-D; TRANSLOCATOR PROTEIN; PERMEABILITY TRANSITION; ABNORMAL INTERACTION; DIVISION DYNAMIN